Pandangan Hadis Tentang Dampak Kecanduan Game Online ‘Mobile Legend’ pada Psikologis (Studi Kasus di Kalangan Remaja Desa Sempajaya Kab.Karo) - Angga Prayuda; Nurliana Damanik; Idris Siregar (Jurnal Manajemen dan Pendidikan Agama Islam, 2025)
In this sophisticated era, the use of mobile phones among teenagers has increased rapidly both for learning and daily needs. Excessive use of mobile phones will have an impact on the lifestyle of teenagers because of playing online games. Therefore, this study aims to determine the impact of online games among teenagers in the perspective of Islam, especially referring to the views of the hadith. The population in this study were teenagers aged 15-17 years who played the online game mobile legend around 4-7 hours or more per day and teenagers who were addicted to the online game mobile legend numbered 5 respondents. This study uses a qualitative method with a case study approach by means of observation and interviews and documentation. The results of the analysis of interviews and observations show that the influence of the online game mobile legend greatly affects the development and growth of teenagers because online games affect the health, psychology, academics, social, and free time that teenagers have is wasted which is detrimental to themselves. Islam does not forbid its people to have fun, but it must remain within the limits and corridors that are determined. The games played should be in accordance with their portion, aka not excessive. Don't let entertainment take up all your time, disrupt your health, hinder other activities, take up study and work time and don't let it distract someone from their main duties, especially in worship, and don't let it make people forget about more important games, such as physical exercise to improve your health or do better activities than being addicted to playing online games. Games also shouldn't make people fall into addiction.